EP1278 Sentinel lymph node technique in early stage ovarian cancer (SENTOV): a phase II clinical trial. (1st November 2019) - Lago, V; Bello, P; Montero, B; Matute, L; Lopez, S; Marina, T; Agudelo, M; Domingo, S
Abstract : Introduction/Background: There is limited evidence that favours the use of the sentinel lymph node (SLN) technique in ovarian cancer. A standardised approach has not been studied. The objective of the present study was to determine the safety and feasibility of the SLN technique by applying a clinical algorithm. Methodology: Twenty patients with histologically confirmed ovarian cancer were prospectively included. 99m Tc and indocyanine green were injected into the ovarian and infundibulopelvic ligament stump. An intraoperative mobile gamma camera, a gamma probe and near-infrared fluorescence imaging were used for SLN detection. Results: The SLN technique was performed in 20 patients. The SLN detection rate at both the pelvic and para-aortic region was 19/20 (95%); this value represented a 100% SLN detection rate at the pelvic and/or para-aortic region. The SLN migration and tracer distribution rates of SLN were 100% for 99m Tc + ICG, 100% for 99m Tc alone and 95% for ICG alone. The mean number of harvested SLNs was 2.2 ± 1.5 (range 0–5) nodes in the pelvic field and 3.3 ± 1.8 (range 1–7) nodes in the para-aortic region. There were no adverse events reported during surgery or the 30-day post-surgery. Conclusion: Detection of SLN in early-stage ovarian cancer appears to be a safe and feasible technique (NCT03452982 ). Disclosure: Nothing to disclose